n-Person Second-Order Games: a paradigm shift in game theory - Larbani, Moussa; Yu, Po Lung (Springer, 2011)
In this paper, we present a new approach to n-person games based on the Habitual domain theory. Unlike the traditional game theory models, the constructed model captures the fact that the underlying changes in the psychological aspects and mind states of the players over the arriving events are the key factors, which determine the dynamic process of coalition formation. We introduce two new concepts of solution for games: strategically stable mind profile and structurally stable mind profile. The theory introduced in this paper overcomes the dichotomy of noncooperative/ cooperative games, prevailing in the existing game theory, which makes game theory more applicable to real-world game situations.